High-stability environment-friendly plywood base material cabinet door plate and preparation method thereof

Through the preparation process of high-stability and environmentally friendly plywood substrate, combined with MDI glue and continuous hot pressing process, the problem of easy deformation of the cabinet door panel is solved, the high stability and environmental protection of the board are achieved, and the production cost and process complexity are reduced.

CN119458537AInactive Publication Date: 2025-02-18DEHUA TB NEW DECORATION MATERIAL CO LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202510069648.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-16
Publication Date
2025-02-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing cabinet door panel materials are prone to deform, resulting in reduced aesthetics of furniture and shortened service life. In the improvement of the existing technology, there are still defects such as complex production processes, high costs and inability to solve the problem of easy deformation from the root.

Method used

Adopt high-stability and environmentally friendly plywood substrates, through veneer carbonization treatment, horizontal assembly, tooth jointing, glue application, blanking, hot pressing and other processes, combined with MDI glue and continuous hot pressing process, reduce the hygroscopicity and internal stress of wood and improve the board dimensional stability and glue strength.

Benefits of technology

It significantly reduces the moisture absorption and internal stress of the cabinet door panel, improves the stability and moisture resistance of the board, extends the service life, and reduces production costs and process complexity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119458537A_ABST
    Figure CN119458537A_ABST
Patent Text Reader

Abstract

The invention discloses a high-stability environment-friendly plywood base material cabinet door plate and a preparation method thereof, the preparation method comprises the processes of single plate carbonization, MDI glue bonding, single plate finishing, staggered joint assembly, plate blank continuous hot pressing and the like, a continuous plate is formed, and the continuous plate can be accurately cut according to the required size. The overall performance of the product is improved, the loss of the carbonized veneer is remarkably reduced, the production process flow is simplified, and the problems that an existing cabinet door plate is poor in stability and prone to deformation are effectively solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of artificial board decorative materials, and in particular relates to a cabinet door panel with a high-stability and environmentally friendly plywood substrate and a preparation method thereof. Background Art

[0002] In the furniture manufacturing industry, cabinet furniture is an indispensable and important part of the bedroom and living space. Its quality and durability are directly related to the consumer's experience and overall satisfaction. However, for a long time, the deformation of cabinet door panels not only affects the aesthetics of the furniture, but also directly shortens the service life of the product, causing unnecessary troubles and losses to consumers. The "shrinkage when dry and swelling when wet" characteristics of wood make it very easy to deform in an environment with large humidity and temperature fluctuations, causing the cabinet door panels to warp and crack during long-term use, seriously affecting the overall performance of the furniture.

[0003] Plywood is a material made by gluing multiple layers of veneer in a crisscross pattern along the grain direction. It has the advantages of high mechanical strength, a strong sense of solid wood, and good nail holding power. However, despite the improvement in the performance of multi-layer boards, there is still a high probability of deformation. In order to solve the problem of easy deformation, people have conducted long-term exploration and proposed various solutions.

[0004] The prior art discloses an anti-deformation cabinet door panel based on eco-board (application number: 202220374046.X), which adopts the method of combining aluminum alloy frame with eco-board to enhance the strength and stability of the cabinet door panel. However, this solution increases the complexity of materials and processing, and may be inconsistent with certain interior decoration styles, affecting the overall aesthetics; the prior art also discloses a compression-resistant and anti-deformation multi-layer furniture panel (application number: 202322015140.3), which proposes a multi-layer furniture panel including a waterproof layer, aiming to enhance the moisture resistance of the panel by using bamboo fiberboard, thereby reducing deformation caused by moisture. However, the materials used in this solution are relatively brittle, which may lead to a weakening of the nail holding force, and the market acceptance is low.

[0005] The improvement measures of the existing technology have alleviated the problem of easy deformation of cabinet door panels to a certain extent, but there are still common defects such as complex production process, high cost, and inability to solve the problem of easy deformation of cabinet door panels from the root. They mostly rely on the use of additional materials to assist in enhancing the performance of the panels. Therefore, there is an urgent need to develop a new method or new material that can not only maintain or improve the performance of the original panels, but also effectively reduce the probability of deformation, so as to meet industry needs and user expectations. Summary of the invention

[0006] The present invention aims to overcome the deficiencies in the prior art and provide a cabinet door panel with a highly stable and environmentally friendly plywood substrate, which solves the problems of poor stability and variability of the cabinet door panel with a relatively simple process.

[0007] A cabinet door panel made of highly stable and environmentally friendly plywood substrate and a preparation method thereof, comprising the following steps: S1, veneer carbonization treatment; The veneer is placed in a carbonization kiln for carbonization treatment; S2, single board horizontal splicing; The carbonized veneers need to be sorted and spliced ​​into the specifications and sizes required for production. Since the carbonized veneers are more brittle and the overall strength is reduced, in order to make the spliced ​​veneers have higher strength, the veneers are spliced ​​horizontally with glue lines; S3, single plate tooth connection; Use a tooth combing machine to punch teeth at the tail and head ends of the veneer after horizontal splicing, and then use a glue coating machine to apply glue to the teeth of the veneer after the teeth are opened. After gluing, the teeth are connected immediately, and then the cold press is cooled and fixed for a few seconds before forming to form a middle plate; S4, board gluing; A vacuum suction cup is used to absorb the entire large single board and put it on the vacuum belt conveyor to avoid damage to the single board caused by manual handling. After the wood chips and debris on the surface are removed by a brush, the glue is applied by atomizing spraying through a spraying device to ensure good glue application uniformity; S5, veneer assembly; The veneer is assembled in odd layers with staggered vertical and horizontal wood grain. After the veneer is assembled, the whole veneer is stacked in a step-like shape, so that it overlaps with the previous veneer slab end to end, and the joints are staggered to avoid overlapping joints that affect the mechanical properties of the finished product. S6, hot pressing of slab; Because the moisture content of the single board is relatively low, microwave preheating is used to achieve rapid heating of the slab from the inside out, and a continuous hot pressing process with a staged temperature decrease is used for forming. The hot pressing temperature decreases step by step, and the highest temperature section does not exceed 220°C. After hot pressing, the first blank board is obtained; S7, plain board processing; After hot pressing, the first raw board is trimmed and beveled before subsequent curing. S8, cardboard lamination; The melamine impregnated adhesive film paper and the high-density board balance layer are laminated by using a conventional high-temperature and high-pressure veneer process; S9, glue coating combination; After the sanded carbonized substrate is evenly coated with adhesive by a glue coating machine, the above-mentioned cardboard balance layer is placed on the upper and lower surfaces of the substrate to obtain a second blank. The amount of glue applied depends on the roughness of the substrate surface. S10, cold pressing: after aging the second slab for a period of time, cold pressing begins, and the specific aging time depends on the temperature and humidity; S11, hot pressing: sending the second slab after cold pressing into a hot press to obtain a second blank slab after hot pressing; S12, edge sawing and curing: after the second plain board is cooled, edge sawing and subsequent curing are performed; S13, sanding: the second plain board after curing is polished with fine sand on the surface by a sanding machine; S14, flat lamination: the sanded second plain board is dusted and then coated with glue by a PUR rubber roller, and the PET film facing is laminated to the second plain board on both sides by a rubber roller; S15, subsequent processing: trimming and cutting after flattening, and subsequent curing treatment.

[0008] Preferably, in the carbonization treatment in step 1, superheated steam is used as the protective gas, the carbonization temperature is 180-220° C., and the carbonization time is 1-2 h; Preferably, in step 1, the moisture content of the wood after carbonization is between 4% and 7%; Preferably, the adhesive used for spraying in step 4 is isocyanate glue, and the amount of glue is 300-350g / m 2 ; Preferably, the overlap width of the end-to-end overlap in step 5 is 20-30 mm; Preferably, the core layer temperature of the slab in step 6 needs to be ≥65°C before entering the continuous hot press, the hot pressing pressure is 3MPa, the hot pressing temperature gradient is 220°C-180°C-150°C-100°C-85°C-50°C, and the upper and lower wedge angles of the inlet of the continuous press need to quickly introduce the slab, and pressurization begins at the entrance section of the press; Preferably, the hot pressing temperature in step 6 is 200° C., the unit pressure is 4-4.5 MPa, and the hot pressing time is 22-25 s; Preferably, the amount of adhesive in step 9 is generally 180-220 g / m 2 (Single-sided), use E0 glue or formaldehyde-free glue, the ratio of glue to flour to curing agent is 10:2.5-3:1; Preferably, the aging time in step 10 is 10-60 min, and the cold pressing unit pressure is 0.3-0.4 MPa and maintained for 60-90 min; Preferably, the hot press in step 11 is maintained at a temperature of 95° C. and a unit pressure of 0.4 MPa for 8 min; Preferably, in step 13, a combined sanding belt with a sanding mesh number of 180-240 mesh is used for surface polishing; Preferably, the coating amount of the PUR adhesive in step 14 is 45-60 g / m 2 .

[0009] The plywood substrate layer of the present invention is subjected to a homogeneous carbonization treatment at 180-220°C, which significantly reduces the hygroscopicity and internal stress of the wood by reducing the water-absorbing hydroxyl groups in the wood tissue, thereby improving the dimensional stability and durability of the wood, and preventing mildew and decay. In view of the problem that the water absorption capacity of the veneer decreases after carbonization treatment and the amount of colloid on the surface of the board is too small to affect the bonding strength, a three-step carbonization method is adopted to ensure the hydroxyl content and moisture content of the wood board after carbonization, and combined with an atomization sizing process, it is ensured that the MDI glue is evenly covered on the surface of the board. MDI glue can enhance the static bending strength of the board, and greatly improves the stability and moisture resistance of the board, and MDI glue does not contain formaldehyde, which is more environmentally friendly and healthy. The present invention introduces a continuous flat pressing process, breaks the traditional Chinese plywood production model, reduces the loss of carbonized veneer, ensures product quality consistency, and greatly improves production efficiency. Finally, the upper and lower surfaces of the processed cabinet door panels are pressed together to set a balance layer to offset the vertical and horizontal mechanical differences and enhance the flatness and structural stability of the board surface; the decorative layer is composed of PET film facing and melamine facing paper to ensure the surface is beautiful and flat. Finally, the processed cabinet door panels have the advantages of low moisture content, low water absorption, stable material, low deformation, high mechanical strength, etc., and have good prospects for industrial application.

[0010] Compared with the prior art, the present invention has the following beneficial effects: 1. MDI bonding technology: It adopts the principle of chemical bonding, through the reaction of -NCO group with wood hydroxyl group and bound water, it provides higher bonding strength than traditional urea-formaldehyde glue, reduces the amount of glue applied to 1 / 5~1 / 6, and does not contain formaldehyde, which significantly improves the environmental protection and performance of the board.

[0011] 2. Phased carbonization treatment: ensure that the veneer is thoroughly carbonized while retaining an appropriate amount of hydroxyl moisture and pores, promote the effective penetration and curing of MDI colloid, and optimize the structural integrity and mechanical properties of the board.

[0012] 3. Continuous hot pressing process: eliminates the manual intervention and waiting time of traditional batch hot pressing, ensures product dimensional stability and surface flatness, reduces defect rate, and improves production efficiency and product quality consistency.

[0013] 4. Double-sided lamination: Use pur glue to double-sidedly laminate the cabinet door panels to avoid the warping problem of the panels caused by single-sided lamination, extend the service life and enhance the aesthetics. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings: Figure 1 This is a schematic diagram of the overlap of the entire single board after assembly; Figure 2 Schematic diagram of a continuous flat press.

[0015] Markings in the figure: 1. Steel belt system (driven roller); 2. Steel belt system (supporting roller); 3. Pressing system (entrance adjustment device); 4. Pressing system (entrance flexible hot pressing plate); 5. Pressing system (oil cylinder); 6. Pressing system (hot pressing plate); 7. Pressing system (frame plate); 8. Pressing system (bottom beam); 9. Steel belt system (circulating steel belt); 10. Roller (chain) blanket system; 11. Steel belt system (driving device); 12. Pneumatic system; 13. Heating system; 14. Hydraulic system; 15. Lubrication system; 16. Electrical system; 17. Cleaning system. DETAILED DESCRIPTION

[0016] In order to facilitate the understanding of the technical solutions of the present invention, the following specific embodiments are described in detail.

[0017] Example 1: Preparation method of highly stable and environmentally friendly plywood-based cabinet door panel A method for preparing a cabinet door panel made of a highly stable and environmentally friendly plywood substrate comprises the following steps: S1, veneer carbonization treatment; The carbonization process is divided into four stages: (1) Rapid heating stage: the eucalyptus veneer is placed in a carbonization kiln for heat treatment. First, the carbonization kiln is rapidly heated to 100°C; (2) High temperature drying stage, the temperature is steadily increased to 150°C, and the heating rate is 2°C / min; (3) Carbonization stage: The temperature of the carbonization kiln is increased to 190°C and maintained for 1 hour, using superheated steam as the heat transfer medium; (4) Cooling stage, finally the temperature is reduced to 80°C and the moisture content of the wood is 4%; S2, single board horizontal splicing; The carbonized eucalyptus veneer is horizontally joined with glue lines, and the size of the board after horizontal joining is 2×4 inches; S3, tooth connection; Small-format veneers use a combing machine to punch teeth at the tail and head ends of the veneers after horizontal splicing, and then use a glue coating machine to glue the teeth of the veneers after the teeth are cut. After gluing, an L-type continuous tooth jointer is used immediately to achieve longitudinal correction, tooth punching, gluing, tooth alignment, tooth pressing cooling, and automatic code alignment. Then, the cold press is cooled and fixed for a few seconds before forming, and multiple medium boards are made. The size of the medium board is 4×8 inches. S4, middle plate gluing; The whole middle board is sucked by a vacuum suction cup and placed on a vacuum belt conveyor. After the wood chips and debris on the surface are removed by a brush, the MDI adhesive is evenly applied to the surface of the eucalyptus veneer by atomizing spraying through a spraying device. The spraying amount is 300g / m 2 ; S5, middle plate assembly; After gluing, the middle plate is assembled in odd layers with vertical and horizontal wood grains. After assembly, the whole middle plate is stacked in a step-like shape, so that it is overlapped with the previous middle plate end to end. The overlap width is 20mm, and the first plate is obtained. The schematic diagram of the overlap of the whole single plate after assembly is as follows Figure 1 As shown; S6, hot pressing of slab; S6.1, microwave preheating; The first slab is quickly heated to 65°C by microwave preheating before hot pressing, and then sent to a continuous hot press; S6.2, hot pressing; A continuous hot pressing process with a staged temperature decrease was adopted, the hot pressing unit pressure was 3MPa, the hot pressing temperature gradient was 220℃-180℃-150℃-100℃-85℃-50℃, and the hot pressing speed was 20s / mm to obtain the first plain board. The schematic diagram of the continuous flat press is shown in the figure. Figure 2 As shown; S7, plain board processing; The size of the first raw board after hot pressing is 1270×2520mm after edge trimming and miter sawing, and then it is cured; S8, cardboard lamination; The melamine impregnated film paper and the high-density board balance layer are placed in a hot press and laminated using a high-temperature and high-pressure veneer process. The hot pressing temperature is 200°C, the unit pressure is 4MPa, and the hot pressing time is 22s. S9, glue coating combination; After the sanded first plain board is evenly coated with adhesive by the glue coating machine, the amount of adhesive is 220g / m 2 (single-sided), using E0 glue, the ratio of glue to flour to curing agent is 3:1; placing the above-mentioned composited cardboard balance layer on the upper and lower surfaces of the substrate to obtain the second blank; S10, cold pressing; After aging the second slab for 30 minutes, cold pressing began, with a unit pressure of 0.3 MPa and a cold pressing time of 60 minutes; S11, hot pressing; The second slab after cold pressing is sent to a multi-layer hot press, with a hot pressing temperature of 95°C, a hot pressing unit pressure of 0.4 MPa, and a hot pressing time of 8 minutes to obtain a second plain plate; S12, sawing edge; After the second blank board is cooled, the excess burrs are removed by sawing machine; S13, sanding; The second raw board after curing is polished with fine sand by a sanding machine, and the sanding number is 240 mesh; S14, flat paste; After the sanding, the second plain board is dusted and then coated with PUR rubber roller, with a coating amount of 50g / m2 , then the PET film facing is laminated to the second plain plate on both sides by a rubber roller; S15, subsequent processing; After flattening, trimming and cutting are carried out to remove burrs, and subsequent curing treatment is carried out.

[0018] The plywood base door panel has a core layer as the base layer, which is made of formaldehyde-free carbonized plywood base material. The upper and lower surfaces of the base layer are laminated with a balancing layer, and the top of the balancing layer is sequentially provided with an impregnated paper layer and a PET film decorative layer from the inside to the outside; its formaldehyde emission is ≤0.008mg / m 3 Reach formaldehyde-free grade, flatness ≤0.15%, bonding strength ≥1MPa, moisture absorption rate ≤5%.

[0019] Comparative Example 1 S1, veneer carbonization treatment; The carbonization treatment temperature rise is divided into three stages. The eucalyptus veneer is placed in the carbonization kiln for heat treatment. First, the carbonization kiln is quickly heated to 100°C, and then the temperature is steadily increased to 150°C. At this temperature, the moisture content of the wood is reduced to 0%, and the heating rate is 2°C / min. After the high-temperature drying is completed, the temperature of the carbonization kiln is increased to 190°C. Superheated steam is used as the heat transfer medium, and the temperature is maintained for 30 minutes; finally, the temperature is reduced to 80°C, and the moisture content of the wood is 4%; The remaining steps are the same as in Example 1.

[0020] The difference between Comparative Example 1 and Example 1 is that in step S1, in the single plate carbonization treatment, the carbonization time is changed from 1 hour to 30 minutes.

[0021] Comparative Example 2 S1, veneer carbonization treatment; The carbonization treatment is divided into three stages. The eucalyptus veneer is placed in a carbonization kiln for heat treatment. First, the carbonization kiln is quickly heated to 100°C, and then the temperature is steadily increased to 150°C. At this temperature, the moisture content of the wood is reduced to 0%, and the heating rate is 2°C / min. After the high-temperature drying is completed, the temperature of the carbonization kiln is increased to 190°C. Superheated steam is used as the heat transfer medium, and the temperature is maintained for 4 hours; finally, the temperature is reduced to 80°C, and the moisture content of the wood is 4%; The remaining steps are the same as in Example 1.

[0022] The difference between Comparative Example 2 and Example 1 is that the carbonization time is changed from 1 h to 4 h.

[0023] Comparative Example 3: Conventional production process for producing plywood-based cabinet door panels A method for preparing a cabinet door panel made of plywood substrate comprises the following steps: S1. Middle board finishing: sort and sort the eucalyptus middle boards, and splice them into long middle boards and short middle boards of required length and width, generally spliced ​​to 1270×2520mm, with moisture content controlled at 12-20%; S2. Gluing of single board: Use roller glue coating machine to glue the middle board, and the glue amount is controlled at 370g / m 2 (double-sided); S3. Assembly of veneers: Assemble the veneers immediately after gluing. During the assembly process, stack them neatly in odd layers with vertical and horizontal wood grains, make full use of the backing and ensure the base is neat; S4, slab cold pressing: after the glue is applied, the slab is placed in a cold press for 0-60 minutes, with a cold pressing pressure of 0.6MPa and a time of 60 minutes; S5. Core repair: Repair the formed slab, cut off the overlap, and fill the missing core. Use plastic gun nails to fix the large missing core, and use masking tape to stick the small area repair in accordance with the specification, without overlap or twisting; S6. Hot pressing of slab: the slab is sent into a multi-layer hot press, the unit pressure of hot pressing is 0.6MPa, the temperature is 130℃, the time is determined according to the thickness of the slab, and the hot pressing time is 1.5-2min / mm; S7, raw board processing: the first raw board after hot pressing is trimmed and beveled according to the required size specifications, and then undergoes subsequent curing; S8, cardboard lamination: put the melamine impregnated film paper and the high-density board balance layer in a hot press, and laminate them using a high-temperature and high-pressure laminating process. The hot pressing temperature is 200°C, the unit pressure is 4MPa, and the hot pressing time is 22s; S9, Glue coating combination: After the first sanded plain board is evenly coated with adhesive by the glue coating machine, the amount of glue is 220g / m 2 (single-sided), the glue is E0 glue, and the ratio of glue to flour to curing agent is 10:2.5-3:1; the above-mentioned composite cardboard balance layer is placed on the upper and lower surfaces of the substrate to obtain the second blank; S10, cold pressing: after aging the second slab for 30 minutes, cold pressing begins, the unit pressure of the cold pressing is 0.3 MPa, and the cold pressing time is 60 minutes; S11, hot pressing: sending the second slab after cold pressing into a multi-layer hot press, with a hot pressing temperature of 95° C., a hot pressing unit pressure of 0.4 MPa, and a hot pressing time of 8 min, to obtain a second plain plate; S12, edge sawing: After the second blank board is cooled, an edge sawing machine is used to saw off the excess burrs; S13, sanding: the second plain board after curing is polished with fine sand by a sanding machine, and the sanding mesh number is 240 mesh; S14, Flat Lamination: After sanding, the second plain board is dusted and then coated with PUR rubber roller, with a coating amount of 50g / m 2Then, the PET film facing is laminated to the second plain board on both sides by a rubber roller.

[0024] The differences between Comparative Example 3 and Example 1 are mainly in two parts. First, the raw material veneer used is ordinary eucalyptus veneer, which has not been carbonized. Secondly, the veneer has not been toothed and is not a whole veneer. There are defects such as core stacking and seam separation, and a subsequent core repair process is required to repair the slab. Second, the production process of the substrate is different. The glue is applied by conventional roller coating and ordinary urea-formaldehyde adhesive, which is not environmentally friendly. Secondly, a conventional periodic hot press is used for hot pressing, and the production efficiency is low.

[0025] Comparative Example 4 The difference between Comparative Example 4 and Example 1 is that the conveyor belt speed during hot pressing of the plate is 60 s / mm; The remaining steps are the same as in Example 1.

[0026] Comparative Example 5 The difference between Comparative Example 5 and Example 1 is that the conveyor belt speed during hot pressing of the plate is 5 s / mm; The remaining steps are the same as in Example 1.

[0027] According to the standard GB / T 34722-2017, the performance parameters of the board were obtained by testing Example 1 and Comparative Example 1, Comparative Example 2, Comparative Example 3, Comparative Example 4 and Comparative Example 5. The results of the physical and chemical properties tests are shown in Table 1: Table 1 Performance parameters of the board

[0028] Compared with Example 1, Comparative Example 1 has a shorter carbonization time, a higher moisture absorption rate of the wood, and a lower bonding strength. Insufficient carbonization time may result in different carbonization degrees on the surface and inside of the veneer, uneven density changes inside the veneer, and usually a more serious shrinkage degree on the surface of the veneer than inside, which may lead to stress accumulation inside the wood, affect the dimensional stability of the veneer, and more easily cause warping or deformation of the board.

[0029] Compared with Example 1, Comparative Example 2 has a longer carbonization time, but the moisture absorption rate of the wood is higher and the bonding strength is weaker. If the carbonization time is too long, the hydroxyl groups will decrease, but the pores inside the veneer will be too small, forming a capillary effect, which will increase the moisture absorption rate instead; too long carbonization time will also cause the pores of the veneer to shrink and break to form cracks, increasing the moisture absorption rate; long-term carbonization treatment will greatly reduce the hydroxyl functional groups in the wood, weaken the glue absorption ability, and less colloid will enter the pores on the surface of the wood board, which will directly affect the effective glue amount at the bonding interface and reduce the bonding strength of the board; it can be seen that after the carbonization time is long enough, the main factor affecting the moisture absorption rate and bonding strength is the pore structure of the wood.

[0030] In comparative example 4, the speed of the conveyor belt was reduced during hot pressing, and the colloid on the surface of the slab solidified before entering the surface pores of the plate. The surface pores were not filled with the colloid, which affected the flatness and dimensional stability of the final plate and made the plate easily deformed.

[0031] In comparative example 5, the conveyor belt speed of the hot press machine is relatively fast, resulting in the hot pressing being completed before the colloid in the core layer of the slab has time to solidify inside the slab, thereby reducing the bonding strength, dimensional stability and flatness of the slab.

[0032] The purpose of the invention is to improve the anti-deformation performance of the plate.

[0033] In the plywood manufacturing process, the factors that affect wood deformation include: (1) the moisture absorption rate of the wood (pore structure and -OH content); and (2) the bonding effect of the adhesive.

[0034] The carbonization process has a direct and significant impact on these two aspects. The process can be divided into three main stages: ① Drying stage, the external water in the wood is removed, followed by -OH condensation, and part of the internal water is removed; the removal of hydrophilic groups greatly reduces the moisture absorption rate of the wood; ② In the initial stage of carbonization, as the temperature rises, the internal water is removed, the small molecule extracts evaporate, and the pores increase. Although the hydroxyl content in the wood decreases at this time, the porous structure makes it possible for the wood to absorb more moisture after cooling, thereby increasing the moisture absorption rate. ③ In the carbonization stage, under the protection of water vapor, the wood becomes dense, the pores become smaller, and the moisture absorption rate of the wood will be reduced to the minimum after cooling. However, if the carbonization stage is excessive, the density of the wood increases, the pores become smaller, and the moisture absorption rate of the wood will increase after cooling. In the prior art, the carbonization time is controlled at 10min-5h. If the time is too short, the carbonization effect cannot be achieved. If the time is too long, the hardness of the wood board will be too high and it will be brittle.

[0035] The reduction of hydroxyl groups and changes in porosity of wood after carbonization will affect the bonding effect of adhesives. Carbonization will reduce the hydroxyl content of wood, reduce the active groups that can react with colloids, and reduce the bonding effect; at the same time, carbonization reduces the porosity, affects the amount of wood impregnation, and reduces the bonding effect of adhesives.

[0036] The hot pressing process has a significant impact on the bonding effect of the adhesive, and the key lies in the matching between the transmission speed of the hot press and the curing conditions. When the transmission speed of the hot press is too slow, the residence time of the sheet in the high temperature zone is prolonged, which causes the surface adhesive to reach the curing temperature first and cure quickly. This surface-preferential curing phenomenon will cause uneven distribution of internal stress, which in turn will cause stress gradients inside the sheet, affecting the flatness of the final product. On the contrary, if the transmission speed is too fast, the residence time of the sheet in the high temperature zone is not enough to complete the full curing process. This may not only cause the adhesive to fail to reach the optimal curing state, but also cause incomplete chemical reactions due to the temperature not meeting the requirements, which will seriously affect the bonding performance. Insufficiently cured adhesives may shrink unevenly during the subsequent cooling process, further increasing the risk of sheet deformation.

[0037] The present invention adjusts the process parameters of carbonization and further explores the influence of carbonization time on the anti-deformation performance of the board. The present invention finds that when the carbonization time is short, only the primary carbonization stage can be entered or completed. Due to the increase in porosity, the wood absorbs water from the air after cooling down, and the moisture absorption rate cannot be reduced well. The high moisture absorption rate will cause the wood to absorb water and deform; but more active groups in the wood can improve the bonding performance of the adhesive. When the carbonization time is long, the hydroxyl groups in the wood can be completely removed and the wood can be densified, but excessive densification will cause a capillary effect to form inside the wood, increasing the moisture absorption rate; excessive densification will cause the adhesive to neither react with the active groups in the wood nor penetrate into the pores of the wood, resulting in poor bonding performance of the adhesive.

[0038] Since the anti-deformation performance is affected by both hygroscopicity and bonding performance, the present invention discusses the influence of the two factors at different stages through experiments.

[0039] According to the experimental results, when the carbonization time is short, the moisture absorption of the active groups in the wood is the main influencing factor of the anti-deformation performance; as the carbonization time increases, the porosity will first increase and then decrease. The porosity affects the moisture absorption rate and bonding performance, and the porosity is the main influencing factor of the anti-deformation performance; when the carbonization time continues to increase, the degree of densification continues to increase, and the capillary water absorption formed will cause the moisture absorption rate to increase, and the bonding performance will be slightly improved, but at this time, the pores are small and few, and the adhesive cannot be impregnated, and the pore size and pore volume become the main influencing factors.

[0040] The present invention further selects the carbonization time to be 1-2 hours, thereby obtaining a plate with better anti-deformation performance.

[0041] In view of the problem of reduced hydroxyl content in wood after carbonization, the present invention selects MDI (diphenylmethane diisocyanate) as a high-performance adhesive. The isocyanate group in MDI glue has high activity and can react not only with hydroxyl groups but also with amino groups (-NH 2), carboxyl (-COOH), thiol (-SH) and other functional groups react to improve the bonding effect. The synergistic effect of carbonization and MDI glue can ensure low moisture absorption and better bonding performance.

[0042] In view of the brittleness of carbonized wood, the present invention introduces a continuous hot pressing process and a segmented block heating method as an effective solution. The present invention adopts a hot pressing process of preheating first and then gradually cooling down. The preheating is to prevent the internal stress caused by the internal and external temperature gradients, and the gradient cooling hot pressing process is to ensure the slow release of water vapor to prevent the board from bursting.

[0043] In the hot pressing process of the present invention, the speed of the conveyor belt is also an important process parameter. A slow transmission speed will lead to a long residence time in the high temperature zone. At this time, the adhesive on the surface layer will solidify first, resulting in uneven internal stress and poor flatness. Too fast a transmission speed will lead to insufficient solidification time and temperature of the core layer of the board, resulting in poor bonding performance. The present invention selects a suitable speed so that the wooden board has a fixed residence time in each temperature section, which effectively avoids material damage or deformation caused by sudden temperature changes and ensures that each piece of board undergoes the same heat treatment conditions. This strategy ensures that the colloid penetrates evenly inside and outside the wood and is fully solidified, thereby improving the quality stability and deformation resistance of the board. The preheating, gradient cooling interval setting and transmission speed of the present invention work synergistically to ensure the deformation resistance of the board.

[0044] The present invention combines the carbonization process, the selection of the colloid and the hot pressing process, thereby not only achieving a faster production speed and a higher output, but also effectively reducing the risk of deformation of the wood board and significantly improving the overall quality of the product.

[0045] The preferred specific embodiments of the present invention are described in detail above. It should be understood that ordinary technicians in the field can make many modifications and changes based on the concept of the present invention without creative work. Therefore, all technical solutions that can be obtained by technicians in the technical field based on the concept of the present invention through logical analysis, reasoning or limited experiments on the basis of the prior art should be within the scope of protection determined by the claims.

Claims

1. A method for preparing a cabinet door panel made of highly stable and environmentally friendly plywood substrate, characterized in that: The method comprises the following steps: a single plate carbonization treatment step, a single plate tooth connection step, a gluing step, a blank assembly step and a blank hot pressing step.

2. The method according to claim 1, characterized in that: In the single plate carbonization treatment step, the carbonization temperature is 180-220° C. and the carbonization time is 1-2 hours.

3. The method according to claim 1, characterized in that In the gluing step, the colloid used is MDI glue.

4. The method according to claim 1, characterized in that: The gluing step is fully automated, using a vacuum suction cup to absorb the entire large single board and place it on a vacuum belt conveyor, and gluing is achieved by atomizing and spraying.

5. The method according to claim 1, characterized in that The assembling step is to assemble the blanks in odd layers with staggered vertical and horizontal wood grains. After the assembling is completed, the whole single board is stacked in a stepped shape, so that it is overlapped end to end with the previous single board blank, and the connecting seams are staggered.

6. The method according to claim 1, characterized in that In the slab hot pressing step, the plate passes through a continuous hot press, and the hot pressing temperature decreases step by step.

7. The method according to claim 6, characterized in that The hot pressing process adopts segmented temperature gradient control, and the hot pressing temperature gradient is 220℃-180℃-150℃-100℃-85℃-50℃.

8. The method according to claim 6, characterized in that The speed of the conveyor belt of the heat press during the heat pressing process is 10-30s / mm.

9. The method according to claim 6, characterized in that Before the hot pressing step, a microwave preheating step is also included, and after preheating, the core layer temperature of the slab is ≥65°C.

10. A cabinet door panel made of a highly stable and environmentally friendly plywood substrate using any one of the methods described in claims 1 to 9, characterized in that: It includes a three-layer structure, which is a balancing layer, a core layer and a balancing layer in sequence; wherein the core layer is carbonized plywood.

Citation Information

Patent Citations

  • Anti-deformation cabinet door plate based on ecological plate

    CN217632087U

  • Compression-resistant and deformation-resistant multi-layer furniture board

    CN220517772U

  • Plywood plate preparation system and method thereof

    CN103737679A

  • Environment-friendly plywood and preparation method thereof

    CN108656249A

  • Preparation process of carbonized fiberboard and application thereof to carbonized composite floor base material

    CN110978190A